A combined process of chemical precipitation and flocculation for treating phosphating wastewater. Issue 53 (13th November 2016) - Zhang, Zhengan; Zheng, Huaili; Sun, Yongjun; Zhao, Chuanliang; Zhou, Yuhao; Tang, Xiaoming; Zhao, Chun
Abstract: A combined process that involves adjusting pH value, adding calcium chloride and flocculation was used for the removals of zinc (Zn), total phosphorus (TP), and chemical oxygen demand (COD) from phosphatizing wastewater. The result of single-factor experiment showed that the optimum process conditions used for precipitation were phosphating wastewater pH (pHI) of 10.0 and CaCl2 dosage of 25.0 g L −1, and for flocculation were cationic polyacrylamide (CPAM) dosage of 20.0 mg L −1 and pH (pHII) of 8.0. Using the optimum process conditions to treat phosphating wastewater, Zn, TP, and COD were reduced to 0.44, 0.33, 38.0 mg L −1, respectively. Response surface methodology (RSM) was employed to optimize the factors of pHI, CaCl2 dosage, CPAM dosage, and pHII to maximize COD removal efficiency. The significant order of factors that affect COD removal efficiency was as CPAM dosage > pHI > CaCl2 dosage > pHII. The interactions between CPAM dosage and pHII, pHI and pHII are relatively significant. The optimization results of RSM experiment showed that the COD removal efficiency of 82.1% could be achieved with the optimal conditions: pHI of 9.5, CaCl2 dosage of 29.0 g L −1, CPAM dosage of 25.2 mg L −1, and pHII of 7.5.